FUNCTIONAL RESULTS IN THE TREATMENT OF PATIENTS WITH SOFT TISSUE INJURIES TO THE VOLAR ASPECT OF THE WRIST - Maljković, Filip; Matić, Slađana (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: The hand is a very important body part with complex anatomy. Important neurovascular structures are located in the hand. Many superficial injuries of the hand, which may at first glance appear harmless, are often associated with injuries to tendons, nerves, and blood vessels. This paper describes soft tissue injuries, while injuries to the bone have been excluded from the study. Aim: The aim of this study is to present the functional outcome of the treatment of patients with soft tissue wounds to the volar aspect of the wrist.Methods: A retrospective analysis of 20 patients treated at the Microsurgery Department of the Emergency Center in Belgrade was performed. We observed the following: gross grip strength (GGS) of the hand, range of motion, the two-point discrimination test (2PD), while the patients filled out the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire.Results: In our study, the GGS of the injured hand was 80.9% of the strength of the uninjured hand. The mean range of motion of the wrist, as well as of the DIP, PIP, and MCP joints, ranged from 77.45% to 91.6%, as compared to the uninjured hand. An S3+ level of sensory recovery was achieved by 10% of patients. The average DASH score was 19.78.Conclusion: Our study shows that proper and timely treatment is necessary for a good functional result in the treatment of these injuries.
Keywords: gross grip strength; mean range of motion; sensory recovery